Visualizing Implicit Queries For Information Management and Retrieval - Czerwinski, Mary; Dumais, Susan; Robertson, George; Dziadosz, Susan; Tiernan, Scott; Dantzich, Maarten Van (CHI 99, 1999)
In this paper, we describe the use of similarity metrics in a novel visual environment for storing and retrieving favorite web pages. The similarity metrics, called Implicit Queries, are used to automatically highlight stored web pages that are related to the currently selected web page. Two experiments explored how users manage their personal web information space with and without the Implicit Query highlighting and later retrieve their stored web pages. When storing and organizing web pages, users with Implicit Query highlighting generated slightly more categories. Implicit Query also led to faster web page retrieval time, although the results were not statistically significant.